THE IMPACT OF GOOD CORPORATE GOVERNANCE MECHANISMS ON FIRM VALUE WITH PROFITABILITY MODERATION VARIABLES - Isdyantanti, Nisa; Wulandari, Ika (Universitas Nusantara PGRI Kediri, 2023)
Research aim: This research aims to investigate the impact of Good Corporate Governance procedures on firm value, using profitability as a moderating variable. The dependent variable in this research is the Good Corporate Governance mechanism, which is represented by the board of commissioners and board of directors. The dependent variable in this research is firm value as defined by Price to Book Value (PBV). Profitability is a moderating variable in this research and is measured using Return on Equity (ROE). This research focuses on pharmaceutical companies listed on the Indonesian Stock Exchange. Design/Method/Approach: This study was carried out using a quantitative approach to test a theory or hypothesis to strengthen or even reject the theory or hypothesis resulting from existing research. The population in this study are pharmaceutical companies registered on the IDX in 2020-2021. This research sample used a purposive sampling method and obtained 55 samples that met the criteria. The data analysis method used in this study was processed using SPSS version 21 software by carrying out multiple regression tests and Moderated Regression Analysis (MRA) tests. Research Finding: According to the findings of this study, the board of commissioners has a considerable impact on corporate value. The board of directors has a substantial effect on the value of the company. Profitability can mitigate the strong influence of the board of directors on firm value. Profitability can reduce the strong impact of the board of directors on firm value. Profitability can thus strengthen the effect of the board of directors and the board of commissioners on corporate value.